Role of the phloem in the biochemistry and ecophysiology of benzylisoquinoline alkaloid metabolism - Lee, Eun-Jeong; Hagel, Jillian; Facchini, Peter (Frontiers in Plant Science, 2013)
Benzylisoquinoline alkaloids (BIAs) are a diverse group of biologically active specialized metabolites produced mainly in four plant families. BIA metabolism is likely of monophyletic origin and involves multiple enzymes yielding structurally diverse compounds. Several BIAs possess defensive properties against pathogenic microorganisms and herbivores. Opium poppy (Papaver somniferum: Papaveraceae) has emerged as a model system to investigate the cellular localization of BIA biosynthesis. Although alkaloids accumulate in the laticifer cytoplasm (latex) of opium poppy, corresponding biosynthetic enzymes and gene transcripts are localized to proximal sieve elements and companion cells, respectively. In contrast, BIA metabolism in the non-laticiferous meadow rue (Thalictrum flavum; Ranunculaceae) occurs independent of the phloem. Evidence points toward the adoption of diverse strategies for the biosynthesis and accumulation of alkaloids as defensive compounds. Recruitment of cell types involved in BIA metabolism, both within and external to the phloem, was likely driven by selection pressures unique to different taxa. The biochemistry, cell biology, ecophysiology, and evolution of BIA metabolism are considered in this context.